The bidirectional biological interplay between microbiome and viruses in periodontitis and type-2 diabetes mellitus - Tang, Boyu; Yan, Caixia; Shen, Xin; Li, Yan (Frontiers in Immunology, 2022)
Periodontitis was an inflammatory disease associated with a dysbiosis of the oral flora characterized by a chronic sustained inflammation inducing the absorption of alveolar bone and leading to tooth loss. Type 2 diabetes mellitus (T2DM) was a metabolic disease caused by impaired insulin action. The oral microbiome played a crucial role in modulating both the innate and adaptive immune system during the trigger and exacerbation of periodontitis and T2DM. The bidirectional relationship of T2DM and periodontitis had been the focus of intensive research, but those were not well explored. In this commentary, an in-depth analysis of the changes of microbiome and bacterial metabolites in periodontitis with or without diabetes was described. The promotion of periodontitis to T2DM might involve inflammatory factors/receptors, oxidative stress, microRNA and so on. The effect of diabetes on periodontitis might involve adipose factor pathway, AGE/RAGE and RANK/RANKL pathway etc. Generally, periodontitis and diabetes are closely related to the microecological-epithelial interaction, soft tissue degradation, bone coupling disorder, immune regulation and gene transcription. The viruses, including HBV, HCV, HSV-1, Coronavirus, HCMV, EBV, HIV, phageome and so on, played an important role in the development of T2DM and periodontitis. An in-depth understanding of the relationship between microbiome and host was of great significance to clarify the bidirectional mechanisms, suggesting that the periodontitis or T2DM remission will have a positive impact on the other.